Pengembangan Program Resitasi Berbantuan Komputer pada Materi Fluida Statis - Askiyah Amalina; Muhammad Reyza Arief Taqwa; Agus Suyudi (Department of Physics Education, Universitas Mataram, 2021)
This research was conducted to develop a computer-assisted recitation program on statics fluid topics The type of research used is R & D (Research and Development) by adapting the Four-D model (Define, Design, Develop, and Disseminate) developed by Thiagarajan, but the research carried out is limited to the develop stage. The product has been validated by 2 media experts in the field of physics education. The feasibility test was carried out on 97 students who took Basic Physics I courses. Based on the results of validation by experts, the average value was 3.74 for content validation and 3.56 for product validation with valid criteria. The feasibility test obtained a proportion of 92.58% in the eligible criteria.